DEVELOPING SPEAKING MATERIAL BASED ON THE TOTAL PHYSICAL RESPONSE (TPR) METHOD FOR THE EIGHT GRADE STUDENT : DEVELOPING SPEAKING MATERIAL BASED ON THE TOTAL PHYSICAL RESPONSE (TPR) METHOD FOR THE EIGHT GRADE STUDENT - Rina Arsanti; Nita Sutanti; Yusniarsi Prismasari (Universitas Islam Balitar, 2023)
The background of the development of speaking material based on Total Physical Response (TPR) is looking at the state of the learning method in general. The objectives of this study analyzed the process of development, validity, practicality, and effectiveness of the method for teaching speaking based on the 2013 of problems: 1) developing speaking material based on Total Physical Response (TPR) for the eighth-grade student. 2) The feasibility the developing speaking material based on the Total physical response (TPR) Method for the eighth-grade student. The researcher applied the research and development (R&D) from Sugiyono (2016). The data were collected in only 8 steps. The subject of this study was VIII B at MTS Syech Subakir Nglegok which consist of 30 students who participated the in the testing activities. The collection techniques used were observation through interviews and Questionaire. Experts’ validation and students learning outcomes tests. While the data analysis techniques used were validity analysis, practical analysis, and effectiveness analysis of learning speaking based on the Total Physical Response (TPR) Method. The results of the design and development show that the model Total Physical Response is valid, the average of the two material experts, media experts, and learning experts is 80%. The test results show that the model is effective. This research was conducted in class VIII MTS Sheikh Subakir Nglegok. The class consists of 30 students involved in the needs analysis and trials that use the method of one experimental design group pre and post-test. The pre-test (57,75) results increase in the post-test (78) results. In the paired sample t-test, the t-count is 17,71 with a t-table of 3,767. The product is valid and can be used as a medium in the teaching and learning proses. The English-speaking material based on Total Physical Response was completed with the teacher and student book. It made the teacher easily use the method. The Total Physical Response (TPR) Method enchanted the students' speaking and Appropriate with the 2013 Curriculum. Keywords: Total Physical Response, Speaking, Teaching Method